Hospital Staff's Perceptions with Regards to the Baby-Friendly Initiative: Experience from a Canadian Tertiary Care Centre. (November 2016) - Pound, Catherine; Ward, Natalie; Freuchet, Marine; Akiki, Salwa; Chan, Jason; Nicholls, Stuart
Background: Adherence to Baby Friendly Initiative (BFI) practices is low in Canadian hospitals, despite evidence showing a positive impact of BFI practices on breastfeeding rates and duration. In 2012, the provincial Ontario Ministry of Health and Long Term Care added BFI status to its progress indicators for Public Health Units, which are now required to begin BFI implementation. Objective: This study aims to explore health care workers' self-reported knowledge of the BFI and their perceptions of the importance of its components. Methods: A questionnaire was electronically sent to 2237 employees working at our institution. Results: Questionnaires were completed by 651 participants, of which 110 (16.9%) and 87 (13.5%) participants reported having good knowledge of the BFI and the Ten Steps to Successful Breastfeeding, respectively. Multiple logistic regression showed that having children and having received formal breastfeeding education were associated with higher self-reported knowledge. Additionally, 481 (75%) participants reported that it was important or very important to them that the institution adopt the BFI. Having children and being an allied health professional were associated with perceiving the implementation of the BFI as important. Conclusion: The results of our study have allowed us to identify potential barriers to implementation of the BFI, which can be targeted through system changes and staff education. Through this approach, we hope to facilitate acceptance of the BFI at our institution and increase support for optimal breastfeeding practices among our patients.